Lactiplantibacillus plantarum-encapsulated microcapsules prepared from okra polysaccharides improved intestinal microbiota in Alzheimer’s disease mice - Hsiao, Yao-Kun; Lee, Bao-Hong; Wu, She-Ching (Frontiers in Microbiology, 2024)
Background Okra contains a viscous substance rich in water-soluble material, including fibers, pectin, proteoglycans, gum, and polysaccharides. This study explored the use of okra polysaccharides by microorganisms and their potential to improve microbiota. Methods The regulation of microcapsules prepared from okra polysaccharides with or without L. plantarum encapsulation on intestinal microbiota was assessed through 16S metagenomic analysis and short-chain fatty acids (SCFAs) in AppNL-G-F/NL-G-F mice (Alzheimer’s disease; AD model). Results We found that Lactobacillaceae and Lactobacillus were majorly regulated by microcapsules prepared from okra polysaccharides in AD mice. Similarly, microcapsules prepared from okra polysaccharides with L. plantarum encapsulation markedly elevated the abundance of Lactobacillaceae and Lactobacillus and increased SCFAs in AD mice. Conclusion Our results suggest that microcapsules prepared from okra polysaccharides with or without L. plantarum encapsulation may improve intestinal microbiota by elevating Lactobacillus levels in AD mice.